Algunas notas sobre neoextractivismo, (pos)neoliberalismo y populismo en Sudamérica (2015)
This paper reflects on present-day South-American sociopolitical reality through three intertwined notions: (post)neoliberalism, populism, and neo-extractivism. It points that the configuration of populist leaderships is merely one of the features to understand the post-neoliberal stage, which is characterized by economic growth heavily dependent upon neo-extractivistic practices that lead to a production of rent from common goods, a part of which is destined to redistribution of income, and by forms of subjectivation and management which are influenced by neoliberal governmental rationality. Therefrom derive the precariousness and ambivalence of the transformations that have been driven by South-American “progressive” governments.